Content Analysis Of Consumer Reviews And Comments On E-Commerce - Simanjuntak, Megawati; Fakhira, Nisrina Nur (Jurnal Doktor Manajemen (JDM), 2023)
Online consumer review (OCR) is a type of E-WOM that may be utilized as a source of information and reference for potential consumers in making decisions. This research utilized mix method design. The quantitative research was successfully conducted using a survey technique using a questionnaire instrument. Moreover, the qualitative research was conducted using content analysis techniques and in-depth interviews. The data obtained were comments that were involved in sentiment analysis. This research indicated that most consumers only provided ratings without being accompanied by reviews. The results also indicated that reviews related to product quality and price were the most discussed by consumers who purchased fashion products. Moreover, some consumers provided inappropriate comments and used repeated words or words that were extended.